PENINGKATAN KETERAMPILAN MEMBAWAKAN ACARA DENGAN MODEL SIMULASI PADA PESERTA DIDIK KELAS VIII A SEMESTER GENAP SMP NEGERI 8 KOTA PEKALONGAN - Nia Ulfa Martha (LPPM Universitas Pekalongan, 2012)
This study aims to improve the skills hosted of students at State Junior High School 8 Pekalongan after applied simulation models. This research approach is quantitative and qualitative. Design research is action research. The process of action research include the first cycle and second cycle. The results showed an increase in skill hosted. The average value and mastery learning has increased significantly. Average value Cycle I is 71 and Cycle II is 81. Observations indicate a change in behavior for the better learners.Learners are more enthusiastic about their lessons and learning becomes fun.Keywords: Skills, Hosted, Model Simulation.